Beyond the Barrel: Azerbaijan’s Strategic Pivot Towards Non-Oil Sector Development and Economic Diversification - Masim Abadov (Modern Scientific Technology, 2025)
For the better part of the last three decades, the economy of the Republic of Azerbaijan has been synonymous with hydrocarbons. The “Contract of the Century,” signed in 1994, unlocked vast oil and gas reserves in the Caspian Sea, propelling the nation into a period of unprecedented economic growth and transforming its infrastructure and geopolitical standing. However, this very reliance on a finite, volatile resource also created a classic “resource curse” scenario—a rentier economy vulnerable to global price shocks, stifled non-oil sector development, and long-term unsustainable growth models.